Quando suspeitar de uma dislipidemia - Bourbon, Mafalda (2016)
The familial dyslipidaemia are under diagnosed and so it is necessary an effort from all health professional to identify these high risk patients in order to provide the best counseling and treatment to reduce their elevated cardiovascular/hepatic/neurologic risk. A novel diagnosis method (by NGS) is being implemented in order to study a larger panel of genes for dyslipidaemia to improve patient diagnosis